Involving employees in six sigma - Hirvonen, Noora (My University, 2016)
Six sigma is a quality improvement philosophy with systematic and formal approach. In order to successfully implement and utilize six sigma the basic disciplines of it should be adopted by the entire organization. Furthermore, employee involvement is crucial in six sigma implementation. This thesis addresses the challenges of long-lasting involvement in the case company. It focuses on gaps of involving six sigma trained employees, Black Belts. Theoretical framework of the thesis illustrates different factors influencing employee involvement. Influencing factors can be divided into ten categories: organizational culture, managerial commitment, leadership style, employee empowerment, employees’ perceptions, communication, training, goals, performance measurement and incentives. Factors and categories overlap and are related to each other. The framework provides holistic view of employee involvement in six sigma context but can be used also with other quality management philosophies. This thesis was conducted as a case study and written on an assignment to a power and automation technology company. Due to the nature of research problem, the data collection was conducted by interviewing case company personnel. In order to study involvement from employees’ point of view interview questions were designed to be open-ended and to allow the interviewees to tell freely about the phenomenon. This thesis provides empirical support on previous studies in organizational support, management commitment and employee empowerment. In addition, it indicates the importance of separate function for Black Belts in the organization. The gaps in Black Belt involvement can be categorized under two categories: Management driven gaps are related to management commitment, organizational structure and culture and information systems. Black Belt driven gaps are related to practice and effort of using six sigma. This thesis finds solutions for bridging these gaps in the case company by applying findings from literature research and suggestions given by the interviewees. For each gap, actions are suggested for bridging the discrepancy between current and desired situations. The thesis states that in order to embed six sigma in the organization the most crucial gaps, lack of management commitment, six sigma vision and possibilities to use six sigma, should be diminished.